Malaysian nasal polyps: eosinophil or neutrophil-predominant - Syuhada O,; Shalini P,; Lim, WK; Ammar A,; Suria Hayati Md Pauzi,; Aneeza Khairiyah Wan Hamizan,; Balwant Singh Gendeh,; Noraidah Masir,; Salina Husain, (Fakulti Perubatan, UKM, 2016)
Eosinophil-type nasal polyp (NP) is common in Western population. This aim of this study was to determine the histology type of NP among different Malaysian ethnic groups. A total of 122 chronic rhinosinusitis with nasal polyposis (CRSwNP) patients were retrospectively enrolled and demographic data was recorded. The histological slides were retrieved. The number of eosinophils and non-eosinophils were counted and average number of inflammatory cells for each high power field was calculated. Eosinophil-predominant was seen in 32.8% of patients and 67.2% was non-eosinophil-predominant. Phenotypes of NP significantly showed an association with ethnicity (x² = 8.322; p < 0.05). A total of 78.9% of Chinese nasal polyps showed non-eosinophil predominant, while Malay and Indian nasal polyps revealed 71.9% and 40.7% of non-eosinophilic phenotype, respectively. Our study showed that Malaysian population had a non-eosinophilic phenotype of nasal polyps. There was a significant association in Malaysian ethnicity with the highest percentage in Chinese population.